Detecting bacteria of the coliform group in the soft tissue of Mytella guyanensis extracted in Cananéia/SP, Brazil - Alessandra Deanna Buono Campos, Fatima; Yoshida Roselli, Larissa; Barbieri, Edison (O Mundo da Saúde, 2020)
This study aimed to evaluate the microbiological quality of water and tissue samples of Mytella guyanensis (Mollusk: Bivalve), a species of relevant commercial interest and is a direct part of the income and food of traditional communities in coastal regions. This study was carried out in two communities in the Cananeia Estuary known as Retiro and Itanhoapina. During the period of 2017, where the species is collected for human consumption, water and bivalve samples were collected in the localities in order to determine the concentrations of total and thermotolerant coliforms. The samples of water and M. guyanensis were analyzed to determine the Most Probable Number (MPN) of Coliforms, based on the Multiple Tube Technique. The results of the analyses showed low concentrations of coliforms in the water samples, with a similar result for the tissue samples of the individuals collected. The water analysis showed a geometric mean of 34.81 total coliforms and 20.70 MPN 100 mL-1 of thermotolerant coliforms. The averages of coliforms in the soft tissues of M. guyanensis were 190 MPN g -1 for total coliforms and 174 MPN g -1 for thermotolerant coliforms. The concentrations of coliforms in the tissue of the collected specimens showed a positive correlation with temperature and a negative correlation with salinity. There were significant differences between seasonality in relation to the concentration of total and thermotolerant coliforms in the tissue. The summer rainy season showed the highest seasonal average of coliforms in M. guyanensis. All values obtained for MPN of coliforms were below the limit established by the legislation.